Longitudinal Faculty Development Program to Promote Effective Observation and Feedback Skills in Direct Clinical Observation - Sheira Schlair; Lawrence Dyche; Felise Milan (Association of American Medical Colleges, 2017)
Introduction We developed a longitudinal faculty development program to maximize faculty training in direct clinical observation (DCO) and feedback, as there was a perceived need for higher quality of DCO and feedback. To achieve this, we created a behaviorally anchored DCO instrument and worked to improve faculty skills in this area. Methods We describe an innovative model of faculty training that is learner centered and reinforces evidence-based principles of effective feedback that are introduced and then repeated in all sessions. The training centers on both peer-led observation of and feedback on faculty learners' recorded DCO feedback encounters, and is guided by our DCO instrument. Residents and faculty completed surveys to assess program impact. Qualitative responses were analyzed for themes. The Wilcoxon signed rank test was used to examine significance of difference in feedback quality before and after DCO faculty development education sessions. Results Our faculty development program has been well received and had a significant impact on quality of faculty feedback, as rated by resident learners. Discussion Our faculty development model is effective at growing faculty learners' DCO and feedback skills. Potential strengths of this program include the use of a behaviorally anchored DCO instrument, longitudinal and experiential faculty development, and use of small-group peer review of recorded faculty feedback encounters. We have found that when their learning needs are attended to, faculty learners cultivate a deep appreciation for principles of effective feedback. In fact, faculty feedback skills can be enhanced in the eyes of resident learners.